COVID-19 encephalopathy, presenting with Broca’s aphasia mimicking stroke - Bhardwaj, Ankit; Sharma, Atma Ram (International Journal of Basic & Clinical Pharmacology, 2022)
Neurological manifestations are emerging as relatively frequent complications of coronavirus disease 2019 (COVID-19), including stroke and encephalopathy. Here we reporting a case of a young male presented with acute aphasia at the emergency department. The patient has a positive history of upper respiratory tract symptoms, subjective fever, and myalgias, a week before for which he was tested positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) based on reverse transcription polymerase chain reaction (PCR) on a nasopharyngeal swab. An electroencephalogram (EEG) demonstrated interictal epileptiform abnormalities over the left posterior frontal lobe. Magnetic resonance imaging (MRI) axial T2- weighted image shows focal area of altered intensity appearing hyperintense involving the left frontotemporal lobes pre-dominantly the pre-central gyrus. A subtle restriction on diffusion-weighted imaging (DWI), with a minimal drop on apparent diffusion coefficient images. In contrast, it shows gyriform enhancement with suspicious adjacent meningeal thickening and enhancement. Cerebrospinal fluid was negative for antibody. Intravenous immunoglobulin (IVIG) 400 mg/kg was given for 5 days. The patient responded well to the therapy without any major clinical side effects and revealed complete resolution after 2 months.